2013
DOI: 10.1111/anae.12261
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internet and simulation‐based training on transoesophageal echocardiography learning in anaesthetic trainees: a prospective randomised study

Abstract: SummaryWith the increasing role of transoesophageal echocardiography in clinical fields other than cardiac surgery, we decided to assess the efficacy of multi-modular echocardiography learning in echo-na€ ıve anaesthetic trainees. Twenty-eight trainees undertook a pre-test to ascertain basic echocardiography knowledge, following which the study subjects were randomly assigned to two groups: learning via traditional methods such as review of guidelines and other literature (non-internet group); and learning via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…Simulation-based learning in TOE is gaining in popularity, with expert opinion reinforcing the results of studies showing benefit when compared with more traditional methods of TOE teaching [8][9][10][11][12][13][14]. The primary objective of this study was to compare the effectiveness of simulationbased and point-of-care TOE training to enable echocardiography-na€ ıve trainees to identify the cardiac anatomy associated with the 20 standard TOE imaging planes.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation-based learning in TOE is gaining in popularity, with expert opinion reinforcing the results of studies showing benefit when compared with more traditional methods of TOE teaching [8][9][10][11][12][13][14]. The primary objective of this study was to compare the effectiveness of simulationbased and point-of-care TOE training to enable echocardiography-na€ ıve trainees to identify the cardiac anatomy associated with the 20 standard TOE imaging planes.…”
Section: Introductionmentioning
confidence: 99%
“…Jerath's study suggested that Virtual TEE was a useful adjunctive tool for learning TEE [17] without hand-on experience Moreover, this team also found that 1 hour training using the virtual TTE simulation is essential for improving the knowledge of navigation among the 20 standard views for the trainees [18]. However, limited number of participants in both studies and no control group may not precisely validate if virtual TEE system can replace traditional TEE methods for training purpose Another prospective randomized study was reported to evaluate the effects of Virtual TEE and simulation-based training on TEE learning for anesthetic trainees [19]. The results showed that trainees who received TEE training via Virtual TEE acquired better image recognition skills compared to those who used traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for Effectiveness of Echocardiography Simulation Several investigators and experts regard the use of echocardiographic simulation as an enhancement and an accelerator to traditional learning programs. [63][64][65][66] A comprehensive description of these studies is beyond the scope of this review; their key features and findings are summarized in table 4. Although most of these studies are underpowered due to the limited sample size, the individual results in these studies highlight a high level of compliance and satisfaction among trainees with the simulation process.…”
Section: Simulation For Echocardiography Educationmentioning
confidence: 99%